'Ye must have faith' how anthropology can contribute to religious heritage: The osteobiography of Italian martyr Saint Nazarius. (14th February 2021) - Biehler‐Gomez, Lucie; Porta, Davide; Mattia, Mirko; De Angelis, Danilo; Poppa, Pasquale; Cattaneo, Cristina
Abstract: The skeletal remains of the alleged Italian Saint Nazarius (1st or 3rd century AD) were examined by a team of anthropologists of the University of Milan upon request from ecclesiastical authorities who sought scientific verification of their authenticity and to add tangible information on the life of the saint. Anthropological analyses were performed for the construction of the biological profile as well as pathological and traumatic analysis and were later compared with historical and hagiographic documentation. In addition, biological sampling of one bone sample was performed for radiocarbon dating. As a result, the osteobiography of the skeletal remains showed a concordance with the available historical data, thus supporting their authenticity and permitted the implementation of further information on the lives of the alleged saint. Furthermore, interesting anatomical 'mistakes' in the postmortem assemblage of the facial bones by the fossores, a guild of gravediggers, morticians and keepers of the Christian catacombs, were noted. This paper discusses the relation between science and religious heritage by demonstrating through a concrete case study the contribution of anthropology in a mutually beneficial collaboration.